PEMBERDAYAAN MASYARAKAT DALAM PROGRAM MAGHRIB MENGAJI DI DESA SUTAWINANGUN KECAMATAN KEDAWUNG - amalia amalia; elina puspa suci elina; muhammad fahmi fahmi; andrifiyatna andri; Sofandi (Al Naqdu, 2023)
The development of an increasingly unstoppable flow of globalization, especially in the field of technology, makes humans increasingly unable to escape from the use of various kinds of technology in carrying out daily activities. But also experienced by people at a young age or children. The use of technological tools or what is known as excessive gadgets has resulted in the erosion of the living culture of traditional communities, such as the loss of community customs and the depletion of religious learning activities, especially in terms of reading the Reciting in madrasas or in mosques which are usually carried out by the younger generation since childhood. . Such as making humans lazy and lazy because they are too dependent on gadgets. Children today are less interested in learning, especially in terms of the Reciting, because they spend too much time playing with gadgets. Therefore, the Cirebon Islamic Religious Institute KKM Students in 2022 carried out mentoring activities with the theme "Maghrib Reciting" especially in the Sutawinangun Village, Kedawung District. The purpose of this program is to revive the spirit of the younger generation in studying and deepening the Islamic religion so that they can take advantage of technological advances in a balanced way and also help other problems such as the lack of teaching staff and the limitations of the teaching methods applied. The method used in this service is field observation.